Effect of Anodic Behavior on Electrochemical Machining of TB6 Titanium Alloy. (10th April 2017) - Liu, Weidong; Ao, Sansan; Li, Yang; Liu, Zuming; Zhang, Hui; Manladan, Sunusi Marwana; Luo, Zhen; Wang, Zhiping
Highlights: A unique phenomenon found in jet ECM is investigated from the viewpoint of anodic behavior. A time-dependent anodic mechanism of pitting/local corrosion/polishing is developed for TB6 titanium alloy in NaCl solution. A novel model is developed to consider the quantitative effect of anodic behavior in simulation. The effect of nozzle travel rate on machining performance is investigated by the novel simulation and experiments to optimize the parameter. Abstract: Jet electrochemical machining is a promising shaping method that has the potential to replace traditional sinking ECM in the industry owing to its flexibility and stability. However, its machining quality is impaired by the occurrence of a unique phenomenon (i.e., the anode cannot be uniformly dissolved with high nozzle travel rate). This paper aims to analyze this unique phenomenon from the viewpoint of anodic behavior and to select the optimum travel rate parameter window. The anodic behavior of TB6 titanium alloy in sodium chloride solution was investigated by linear sweep voltammetry, cyclic voltammetry, electrochemical impedance spectroscopy and chronoamperometry. A time-dependent mechanism of pitting/large localized corrosion/polishing for the anodic interface structure was developed. The full electricity quantity of the equivalent oxide layer capacitor, Q, was proposed as a criterion for the initiation of uniform dissolution state. Subsequently, a novel model that incorporates the parameter Q was developed to account for the effect of anodic behavior. This model is able to predict the machined profile as well as the localized corrosion range. Finally, the effect of nozzle travel rate on jet ECM performance was investigated, and a nozzle travel rate of 10 to 25 μm s −1 was selected as the optimum parameter window in the present work.